PERAN KEPEMIMPINAN DALAM PEMBERDAYAAN TENAGA PENDIDIK - Rastiana; Winda Nopriani; Muhammad Sirozi (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
Education in the digital era demands professional, adaptive, and innovative educators. Empowering educators has become a crucial strategy for improving the quality of national education. This study aims to analyze the central role of leadership in the process of empowering educators in educational institutions. The method used is a library research with a descriptive qualitative approach. Data were collected from various scientific journals, books, and relevant literature sources which were then analyzed in depth. The results show that leadership, especially transformational leadership, plays a vital role as a motivator, facilitator, and visionary. An effective leader is able to create a conducive work climate, encourage competency development, provide autonomy, and build a collaborative culture. Effective empowerment strategies identified include continuous training, delegation of trust and responsibility, and the implementation of constructive appreciation and feedback systems. Successful empowerment has a direct impact on increasing the competence, motivation, and professionalism of educators, which in turn contributes to improving the quality of student learning. Keywords: leadership; empowerment; educators; transformational leadership